Dark, bright and other optical solitons to the decoupled nonlinear Schrodinger equation arising in dual-core optical fibers - Baskonus, Haci Mehmet; Sulaiman, Tukur Abdulkadir; Bulut, Hasan (Springer, 2018)
The dynamical systems of soliton propagation through optical fibers for transcontinental and trans-oceanic distances is one of the most interesting areas of study. Optical solitons are restrained electromagnetic waves that stretch in nonlinear dispersive media and allow the intensity to remain unchanged due to the balance between dispersion and nonlinearity effects. In this study, we successfully acquire dark, bright, combined dark-bright, singular and combined singular soliton solutions to the decoupled nonlinear Schrodinger equation arising in dual-core optical fibers by using the extended sinh-Gordon equation expansion method. The constraint conditions for the existence of valid soliton solutions are given. We discuss how change in parameters affect the solitons transmission. We present the 2D, 3D and the contour graphs to some of the reported solutions.
Keywords: The extended ShGEEM; Optical fibers; The decoupled NLSE; Optical solitons